INTEGRATION OF TRI HITA KARANA VALUES IN DIFFERENTIATED LEARNING AND ITS IMPACT ON SOCIAL ATTITUDES AND IPAS LEARNING OUTCOMES IN ELEMENTARY SCHOOL STUDENTS - Ni Nyoman Kurnia Wati; I Made Hendra Sukmayasa (Program Studi PGSD Universitas Flores, 2025)
Social attitudes and IPAS learning outcomes among fifth-grade students necessitate improvement. Observations indicate a lack of student engagement, underdeveloped collaborative skills, limited participation in discussions, and persistent low scores below the minimum competency criteria on reassessments. Consequently, this research was conducted to analyze the influence of differentiated instruction integrated with Tri Hita Karana (THK) principles on the social attitudes and IPAS learning outcomes of fifth-grade students within Cluster III, Buleleng District. This study employed a quasi-experimental design with a post-test-only control group. The population comprised 284 students, from which a sample of 71 students was selected using simple random sampling. The independent variable was differentiated instruction incorporating THK, while the dependent variables were social attitudes and fifth-grade IPAS learning outcomes. Data were collected through observation for social attitudes and tests for IPAS learning outcomes. Quantitative descriptive and inferential statistical analyses, specifically Multivariate Analysis of Variance (MANOVA), were utilized for data analysis. The findings revealed significant F values in the Corrected Model section for social attitudes (F = 40.187) and IPAS learning outcomes (F = 17.168), as well as significant multivariate test statistics for Pillai's Trace, Wilks' Lambda, Hotelling's Trace, and Roy's Largest Root (F = 29.250). Therefore, it can be concluded that: (1) differentiated instruction infused with THK significantly influences students' social attitudes; (2) differentiated instruction infused with THK significantly influences students' IPAS learning outcomes; and (3) concurrently, differentiated instruction infused with THK has a significant impact on both students' social attitudes and IPAS learning outcomes.